Mediating governmentality during Covid – 19: A principal's task. Issue 1 (2020) - Bradley, Matthew; Sellars, Maura
Abstract: The identification and aggressive, deadly spread of the coronavirus, known as Covid −19 has impacted on societies across the world. It has no modern precedent and has forced decision making at all levels of government to be increasingly reactive and impose restrictions, mandated closures and to disrupt everyday lives in order to provide some degree of safety for the communities they serve. Schools have not been exempt from these disruptions, with many countries deciding to close their school indefinitely and to supervise only students whose parents are in essential services. The decision made by Australian government authorities not to close the nation's schools in the face of the pandemic created considerable dilemmas and demands for their entire communities and provided an example of Foucault's (1991) notion of governmentality in action. This work, utilizing an autoethnographic research approach and Leithwood's Four Path Framework, describes how one principal in a regional town in New South Wales met the challenges of the mandates to provide multicontextual, equitable educational opportunities for students, to support his unprotected staff, to maintain school values and standards and to increase the sense of belonging, hope and purpose in his community. The success of these strategies is evidenced in the feedback of staff and the school community.